Identification of thrombin-like activity in ovarian cancer associated ascites and modulation of multiple cytokine networks - Naldini, Antonella; Morena, Emilia; Belotti, Dorina; Carraro, Fabio; Allavena, Paola; Giavazzi, Raffaella (Thrombosis and Haemostasis, 2011)
Blood coagulation cascades can be activated by different mechanisms and to different levels in cancer patients. In a study conducted on the transcriptional profile of epithelial ovarian cancer patients a number of possible links between coagulation and inflammation have been suggested and we and others have reported that, in addition to its central role in blood coagulation and haemostasis, thrombin is a powerful regulator of inflammatory responses. Here, we report that thrombin-like activities were present in the malignant ascites of patients with ovarian carcinoma. Malignant ascites significantly enhanced the release of cytokines/chemokines, which have been previously shown to support tumour progression, such as interleukin (IL)-6, IL-1β, CCL2 and CXCL8, in human peripheral blood mononuclear cells of healthy volunteers. Interestingly, ascites enhanced the release of the anti-inflammatory cytokine IL-10 and inhibited the production of interferon-γ and IL-12. The presence of the anticoagulant antithrombin reversed IL-12 inhibition induced by ascites in human monocytes. Finally, the use of thrombin and of the specific thrombin receptor (PAR) agonist peptides, TFLLRN and AYGPK, suggests that IL-12 inhibition is thrombin-specific and related to PAR-1, but not to PAR-4. These findings underline the tight relationship between the coagulation pathway, where thrombin is the key enzyme, and cytokine modulation, including IL-12 inhibition, which is a critical feature of the tumour microenvironment, and may represent a powerful strategy used by tumours to escape immune surveillance.
Keywords: Thrombin; cytokines; inflammation; coagulation; tumour microenvironment